(untitled) (Universal International Scientific Journal, 2026)
The role and importance of national education in the context of neurodigital civilization, when the minds of young people are increasingly influenced by a powerful flow of information, digital technologies, and global ideological influences, is analyzed. The main goal of the study is to identify effective mechanisms for the formation of cognitive-ideological resistance in young people based on national values, traditions, and spiritual heritage.